PENERAPAN PRINSIP TRANSPARANSI BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBERDAYA MANUSIA DALAM PELAKSANAAN REKRUTMEN PPPK DI KABUPATEN MUNA BARAT - Suriyani BB; Asriani; La Ode Muhammad Elwan; Risky Wilda Yanti (Halu Oleo University, 2024)
This study aims to determine how the Application of the Principles of Transparency of the Civil Service Agency and Human Resource Development in the Implementation of PPPK Recruitment in West Muna Regency. The method used in this research is descriptive qualitative research with data collection through observation, interviews, and documentation. Based on the research results, The implementation of the principle of transparency in the BKPSDM of West Muna Regency in the implementation of PPPK recruitment has been running but not yet optimal. Although tasks have been carried out well, the late response to information and the difficulty of the community in understanding the registration procedures and accessing information through the website show that transparency still needs to be improved. In general, the provision of clear information and easy access to information are still areas that need improvement to ensure effective transparency.